2020
DOI: 10.1007/s10980-020-01046-0
|View full text |Cite
|
Sign up to set email alerts
|

Nonparametric machine learning for mapping forest cover and exploring influential factors

Abstract: The contribution of forest ecosystem services to human well-being varies over space following the dynamics in forest cover. Use of machine learning models is increasing in projecting forest cover changes and investigating the drivers, yet references are still lacking for selecting machine learning models for spatial projection of forest cover patterns. ObjectivesWe assessed the ability of nonparametric machine learning techniques to project the spatial distribution of forest cover and identify its drivers usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 74 publications
(80 reference statements)
2
3
0
3
Order By: Relevance
“…Also, in a study in Western Himalaya [76] that used machine learning methods including classification regression tree (CART), random forest (RF), and support vector machine (SVM) algorithms showed results similar to the present study; the authors concluded that RF model has a higher accuracy in forest fire burn area. A study in Tasmania, Australia [77] used support vector regression (SVR), artificial neural networks (ANN), random forest (RF), and gradient boosted regression trees (GBRT) for mapping forest cover and exploring influential factors, and their findings were in line with the results of our study. In terms of projection accuracy, and required less computational costs, RF far outperformed the other three models [77].…”
Section: Machine Learning Approach To Modeling Diversitysupporting
confidence: 81%
See 1 more Smart Citation
“…Also, in a study in Western Himalaya [76] that used machine learning methods including classification regression tree (CART), random forest (RF), and support vector machine (SVM) algorithms showed results similar to the present study; the authors concluded that RF model has a higher accuracy in forest fire burn area. A study in Tasmania, Australia [77] used support vector regression (SVR), artificial neural networks (ANN), random forest (RF), and gradient boosted regression trees (GBRT) for mapping forest cover and exploring influential factors, and their findings were in line with the results of our study. In terms of projection accuracy, and required less computational costs, RF far outperformed the other three models [77].…”
Section: Machine Learning Approach To Modeling Diversitysupporting
confidence: 81%
“…A study in Tasmania, Australia [77] used support vector regression (SVR), artificial neural networks (ANN), random forest (RF), and gradient boosted regression trees (GBRT) for mapping forest cover and exploring influential factors, and their findings were in line with the results of our study. In terms of projection accuracy, and required less computational costs, RF far outperformed the other three models [77].…”
Section: Machine Learning Approach To Modeling Diversitysupporting
confidence: 81%
“…Moreover, they are context-sensitive, and require expert knowledge in specific fields and substantial efforts in maintaining rules and dictionaries. To overcome these drawbacks, the Hidden Markov Hodel (HMM), the maximum entropy model (MaxEnt), the Conditional Random Field (CRF), and classical machine learning methods such as the support vector machines [12] have gradually replaced the aforementioned traditional methods.…”
Section: Introductionmentioning
confidence: 99%
“…Ressalta-se que a simples extração da informação dos sensores hiperespectrais ou a utilização de índices espectrais de vegetação, não permitem de forma simples a distinção de variedades de cana, não gerando resultados satisfatórios(FRASSON et al, 2007;. Nestes casos é necessário o uso de técnicas de aprendizagem de máquinas, as quais têm grande vantagem ao analisar dados com alta dimensionalidade, não lineares, provendo assim uma melhor acurácia(PARK et al, 2014;LIU et al, 2020). Tais técnicas vem sendo empregadas em diversas que as demais técnicas(LIU et al, 2020).…”
unclassified
“…Nestes casos é necessário o uso de técnicas de aprendizagem de máquinas, as quais têm grande vantagem ao analisar dados com alta dimensionalidade, não lineares, provendo assim uma melhor acurácia(PARK et al, 2014;LIU et al, 2020). Tais técnicas vem sendo empregadas em diversas que as demais técnicas(LIU et al, 2020). Outra questão importante é com relação ao número de amostras que, quando reduzidas em comparação ao número de variáveis, podem acarretar performance ruim do modelo, o que eventualmente é resolvido com técnicas de redução de dimensionalidade, como a análise de componentes principais (PCA).…”
unclassified